Regulasi Emosi dan Penyesuaian Mahasiswa Baru Saat Pandemi: Pentingkah Dukungan Emosional Orang Tua? - Yunissa Meganingtyas; Dian Mufitasari (Gadjah Mada Journal of Psychology (GamaJoP), 2022)
The Covid-19 pandemic has made new students of the class of 2020 experience three transitions at once in their lives. It takes a good ability to regulate emotions so that new students are able to pass the transition period successfully. This study aims to examine the role of emotion regulation on the ability to adjust to college during a pandemic through the emotional support of parents as moderators for new students. A total of 247 new students from the 2020 batch of Gadjah Mada University participated voluntarily in filling out the online questionnaire. There are three measuring tools used, namely the Emotion Regulation Scale, Student Adaptation to College Questionnaire (SACQ), and the Parental Emotional Support Scale. Moderation Regression Analysis was used to test the hypothesis and the results showed that parental emotional support was not proven to moderate the relationship between emotional regulation and college adjustment. However, emotion regulation was shown to have a direct positive effect on academic and social adjustment (p < 0.05).